Using the multi-ethnic group measure as an indicator of Malaysian ethnic identities - Granhemat, Mehdi; Chan, Swee Heng; Abdullah, Ain Nadzimah (Malaysian Association of Modern Languages, 2014)
Understanding ethnic identity has gained increasing theoretical, empirical, and practical salience in Malaysia due to developments in economics, national desires and social structure of society. Social psychologists’ interest in identity is centred on feelings of belonging to a group and the consequences of identification with one’s social groups in society (Tajfel & Turner, 1986). This study examined ethnic identity among undergraduate students of a public university in Malaysia. Data were collected via a survey questionnaire (the Multi Ethnic Group Measure) from 498 undergraduates who were studying at 15 different faculties of the university. Findings of the study can add to the knowledge base for studying ethnic identity in that there is variability in trajectories among ethnic groups in different geographical locations and most importantly, the study confirmed that ethnic identity can be measured.